2003
DOI: 10.1038/sj.bjc.6601130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aplidin in acute lymphoblastic leukaemia cells

Abstract: The cytotoxic effect of Aplidin was investigated on fresh leukaemia cells derived from children with B-cell-precursor (BCP) acute lymphoblastic leukaemia (ALL) by using stromal-layer culture system and on four cell lines, ALL-PO, Reh, ALL/MIK and TOM-1, derived from patients with ALL with different molecular genetic abnormalities. In ALL cell lines Aplidin was cytotoxic at nanomolar concentrations. In the ALL cell lines the drug-induced cell death was clearly related to the induction of apoptosis and appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 27 publications
2
32
0
1
Order By: Relevance
“…Aplidine inhibits endothelial cell proliferation, with an IC 50 similar to that observed for tumour cells. Other studies reported that concentrations of aplidine that completely inhibited colony formation by cancer cells were almost ineffective on bone marrow and cord blood haematopoietic progenitor cells, nonstimulated lymphocytes and hepatocytes (Sakai et al, 1996;Gomez et al, 2001;Albella et al, 2002;Erba et al, 2003;Gajate et al, 2003). In agreement, we found that the concentrations of aplidine that affected endothelial cell proliferation had no relevant antiproliferative effect on epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Aplidine inhibits endothelial cell proliferation, with an IC 50 similar to that observed for tumour cells. Other studies reported that concentrations of aplidine that completely inhibited colony formation by cancer cells were almost ineffective on bone marrow and cord blood haematopoietic progenitor cells, nonstimulated lymphocytes and hepatocytes (Sakai et al, 1996;Gomez et al, 2001;Albella et al, 2002;Erba et al, 2003;Gajate et al, 2003). In agreement, we found that the concentrations of aplidine that affected endothelial cell proliferation had no relevant antiproliferative effect on epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…In vitro, aplidine inhibited tumour cell proliferation with an IC 50 in the nanomolar/subnanomolar range, with complete inhibition achieved at 10 nM (Lobo et al, 1997;Erba et al, 2002;Erba et al, 2003). Short-term exposure to aplidine rapidly caused apoptosis of tumour cells (Erba et al, 2002;Gajate et al, 2003) and prevented the formation of colonies by explanted tumour cells (Depenbrock et al, 1998).…”
mentioning
confidence: 99%
“…Aplidin is an extremely potent inducer of apoptosis, with concentrations that caused 50% inhibition of tumour growth (IC 50 ) in vitro in a low nanomolar range, and it also exhibits strong antitumor activity in xenograft models (Urdiales et al, 1996;Erba et al, 2002;Broggini et al, 2003;Biscardi et al, 2005). In different haematological malignancies, such as acute lymphoblastic leukaemia, acute myeloid leukaemia and lymphoma, the drug is cytotoxic on primary human cells and cell lines, even on leukaemic cells carrying cytogenetic abnormalities that have poor prognostic implications (Bresters et al, 2003;Erba et al, 2003;Gajate et al, 2003). In addition to the cytotoxic properties of Aplidin, the molecule exhibits also strong antiangiogenic activity.…”
mentioning
confidence: 99%
“…Sabe-se que seus efeitos implicam principalmente no bloqueio da divisão celular (devido à inibição da síntese de DNA e proteínas) e no enfraquecimento da angiogênese tumoral (pela diminuição da secreção de VEGF e da expressão do receptor VEGF-r1 e à inibição da enzima ornitinadescarboxilase). [99][100][101] A aplidina foi licenciada para a PharmaMar sob o registro de Aplidin ® (plitidepsina) e ingressou nos testes clínicos em 1999, vindo a se beneficiar diretamente das informações geradas nos estudos com didemnina B. Interessantemente, a simples oxidação do radical 2-hidroxipropanoil a 2-oxopropanoil transforma substancialmente o seu perfil toxicológico. 10,30 De modo geral, o tratamento com aplidina tem sido bem tolerado e a toxicidade neuromuscular, seu principal fator limitante, pode ser contornada com a coadministração de L-carnitina.…”
Section: Prialt ® (Ziconotídeo ω-Conotoxina Mviia)unclassified